Active region of CdTe X-/γ-ray detector with Schottky diode - Kosyachenko, L.A.; Maslyanchuk, O.L. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
It has been shown from the Poisson equation that the presence of deep levels in the semiconductor bandgap influences in a complicated manner upon distribution of the space charge, potential and electrical fields in the Schottky diode. Under high reverse bias, however, the diode characteristics become standard. To achieve semi-insulating conductivity in CdTe, it is impossible to widen considerably the depleted layer in the diode. Therefore, the region of the high electric field is only a small part of the substrate thickness. Too small capacitance value and its weak dependence on the bias voltage observed in the Schottky diode made of semi-insulating CdTe are a result of the effect of the substrate resistance and the wide space charge region in the diode.